Experimental Study on Shear Resistance of Carex-Root-Fibered Soil - Feng-Chi Wang; Ming-Ze Zhao; Qi Sun (Advances in Civil Engineering)
Carex shows strong vitality, adaptability, and performance with regard to soil consolidation and slope protection but is often disregarded as a weed. This study proposes to turn this so-called weed into treasure, using its characteristics to protect the slope. We studied the interaction between the carex roots and soil and compared it to other types of grass. To understand the interaction between the carex roots and soil, this study investigated the tensile properties of the carex root fibers. The effects of fiber content, humidity, distribution, and soil moisture content on the relationship between the shear strength and vertical pressure of the soil were analyzed using a direct shear test. Furthermore, the cohesion and internal friction angle were used to evaluate the shear strength of the root-fibered soil based on Mohr–Coulomb’s law. The results showed that the smaller the diameter, the shorter the length, and the greater the quantity and the lower the humidity of the root fibers, the higher the tensile strength of root fibers. In addition, the soil strength could be improved by the joint action of the roots and the soil. With an increase in the root fiber content and humidity, the soil moisture content decreased, whereas the shear strength of the carex-root-fibered soil increased. Here, four kinds of root fiber distributions, namely, “glyph,” “herringbone,” “eccentric,” and “vertical,” were chosen to study the shear strength of the root-fibered soil. The results showed that “glyph” root fiber distribution had the highest shear strength, while the shear strength decreased for the others.